Employees’ Performance Review at the Office of the District of IDANO TAE-NIAS Selatan and the Variables That Influence IT - Duha, Timotius (IJBLE Scientific Publications Community Inc., 2025)
This study aims to determine the effect of three independent variables in this research model on the performance of employees at the Idano Tae sub-district office in South Nias Regency. All employees (30 people) in the research object are designated as respondents. The type of data is primary data, data collection using a questionnaire distribution method which is then processed with the help of Smart PLS software. The analysis tool used is simple and multiple linear regression. The results of partial testing show that the t count value ≥ t table value, (work environment and discipline on performance. While for the partial test of motivation on performance t count ≤ t table value. Simultaneous testing shows that the three independent variables together have a positive effect on performance.